HUGE VARIATIONS IN THE ISOTOPIC RATIO 196HG 202HG IN SOME ACID-INSOLUBLE RESIDUES OF SIKHOTE ALIN AND OTHER IRON METEORITES - Thakur A.N.; Goel P.S. (My University, 1989)
The insoluble materials obtained on dissolution of iron meteorites in 2 M H2SO4 have been analyzed by radiochemical neutron activation to measure the isotopic ratio Hg-196/Hg-202 of Hg released at different temperatures. In many cases this ratio is found to be anomalous; its extreme values, relative to the reagent Hg, being: less than 0.003 (2sigma limit) and 1.26 + or - 0.05. Often, in the same residue, both positive and negative deviations are found at different temperatures. The anomalous, normal, and isotopically diluted Hg distillates have been re-irradiated to eliminate the influence of neutron self-shielding and interfering reactions from matrix elements. The isotopic anomaly persists in the distillates, proving that any artifacts during irradiation are essentially absent.